2017
DOI: 10.1111/aos.13515
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to retinal haemorrhage in infants born at high risk

Abstract: The incidence of RH in high-risk infants was 18%, and delivery mode, and neonatal asphyxia were major risk factors for RH in high-risk infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…In this study, vaginal delivery was a risk factor for neonatal retinal hemorrhage. Previous studies have also reported that vaginal delivery is significantly associated with neonatal retinal hemorrhage [ 1 , 4 , 6 , 8 , 12 , 26 , 29 , 30 , 31 , 34 ]. Callaway et al found that 29.6% of babies delivered vaginally exhibited retinal hemorrhage, compared to 5.2% of babies delivered by cesarean section [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, vaginal delivery was a risk factor for neonatal retinal hemorrhage. Previous studies have also reported that vaginal delivery is significantly associated with neonatal retinal hemorrhage [ 1 , 4 , 6 , 8 , 12 , 26 , 29 , 30 , 31 , 34 ]. Callaway et al found that 29.6% of babies delivered vaginally exhibited retinal hemorrhage, compared to 5.2% of babies delivered by cesarean section [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, China, which has a large population with an annual birth rate of 12% [ 28 ], has limited data on neonatal retinal hemorrhage [ 29 , 30 , 31 , 32 , 33 ], and the few existing studies have not fully evaluated the risk factors associated with mothers and newborns. Moreover, the descriptions of the characteristics of retinal hemorrhage are not sufficiently detailed, which limits our knowledge of the condition and the development of prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral, extensive bleeding in several retinal layers has been regarded as a key feature of abusive head trauma [ 6 , 7 , 36 , 41 , 42 , 53 , 56 ]. However, RH may not be pathognomonic for abusive head traumas; they can also be seen in infants not related to abuse, e.g., in a large number of healthy newborns [ 37 , 50 , 70 ], in infants with “macrocephaly” [ 55 , 64 ], after “high-risk” deliveries [ 58 ], following acute life-threatening events [ 5 ], and after cardiopulmonary resuscitation [ 33 , 54 , 57 ]. RHs have also been documented in premature infants; contrary to the rapid resolution of the bleeding one usually sees in most newborns, the bleeding in preterms tend to be long lasting [ 18 ].…”
Section: Clinical and Radiological Findingsmentioning
confidence: 99%
“…There are also reports showing RH was higher for younger mothers < 22 years old, which may possibly be the result of greater birth canal resistance due to primiparity, uterine inertia and insufficient force of labour, longer stages of labour, and an external force (obstetric forceps or vacuum) but in contrary to these studies, in our study there showed no clinically significant association between maternal age and neonatal RH. 12 In regards to birth weight, our study showed that larger birth weight had clinically significant association with retinal haemorrhage. This could be due to the fact that there is greater birth canal resistance during birth.…”
Section: Discussionmentioning
confidence: 52%
“…9 Though, in a survey of high-risk factors affecting retinopathy in full-terms infants in China showed a lower incidence of 18%. 1,6,12 Nevertheless, the incidence rate of neonatal retinal haemorrhage has shown to vary from 2.6 to 50%. 3,4 In our study majority of the retinal haemorrhage were of grade 1 according to Classification Degree of Neonatal Retinal Haemorrhage based in Egge et al 8 This contradicted to study by Qinglan et al where they had almost equal distribution of all grades of retinal haemorrhage.…”
Section: Discussionmentioning
confidence: 99%